Enoxaparin ameliorates post–traumatic brain injury edema and neurologic recovery, reducing cerebral leukocyte endothelial interactions and vessel permeability in vivo. Issue 1 (July 2015) - Li, Shengjie; Marks, Joshua A.; Eisenstadt, Rachel; Kumasaka, Kenichiro; Samadi, Davoud; Johnson, Victoria E.; Holena, Daniel N.; Allen, Steven R.; Browne, Kevin D.; Smith, Douglas H.; Pascual, Jose L.
Abstract : BACKGROUND: Traumatic brain injury (TBI) confers a high risk of venous thrombosis, but early prevention with heparinoids is often withheld, fearing cerebral hematoma expansion. Yet, studies have shown heparinoids not only to be safe but also to limit brain edema and contusion size after TBI. Human TBI data also suggest faster radiologic and clinical neurologic recovery with earlier heparinoid administration. We hypothesized that enoxaparin (ENX) after TBI blunts in vivo leukocyte (LEU) mobilization to injured brain and cerebral edema, while improving neurologic recovery without increasing the size of the cerebral hemorrhagic contusion. METHODS: CD1 male mice underwent either TBI by controlled cortical impact (CCI, 1-mm depth, 6 m/s) or sham craniotomy. ENX (1 mg/kg) or vehicle (VEH, 0.9% saline, 1 mL/kg) was administered at 2, 8, 14, 23, and 32 hours after TBI. At 48 hours, intravital microscopy was used to visualize live LEUs interacting with endothelium and microvascular leakage of fluorescein isothiocyanate–albumin. Neurologic function (Neurological Severity Score, NSS), activated clotting time, hemorrhagic contusion size, as well as brain and lung wet-to-dry ratios were evaluated post mortem. Analysis of variance with Bonferroni correction was used for statistical comparisons between groups. RESULTS: Compared with VEH, ENX significantly reduced in vivo LEU rolling on endothelium (72.7 ± 28.3 LEU/100 μm/min vs. 30.6 ± 18.3 LEU/100 μm/min, p = 0.02) and cerebrovascular albumin leakage (34.5% ± 8.1% vs. 23.8% ± 5.5%, p = 0.047). CCI significantly increased ipsilateral cerebral hemisphere edema, but ENX treatment reduced post-CCI edema to near control levels (81.5% ± 1.5% vs. 77.6% ± 0.6%, p < 0.01). Compared with VEH, ENX reduced body weight loss at 24 hours (8.7% ± 1.2% vs. 5.8% ± 1.1%, p < 0.01) and improved NSS at 24 hours (14.5 ± 0.5 vs. 16.2 ± 0.4, p < 0.01) and 48 hours (15.1 ± 0.4 vs. 16.7 ± 0.5, p < 0.01) after injury. There were no significant differences in activated clotting time, hemorrhagic contusion size, and lung water content between the groups. CONCLUSION: ENX reduces LEU recruitment to injured brain, diminishing visible microvascular permeability and edema. ENX may also accelerate neurologic recovery without increasing cerebral contusion size. Further study in humans is necessary to determine safety, appropriate dosage, and timing of ENX administration early after TBI.